Vacuum rectification of salvia sclarea essential oil - Чепель, Наталія Василівна (Technology audit and production reserves, 2014)
The issue of carrying out a vacuum rectification of essential oils with obtaining planned fractions of various aromatic properties was considered and some results of our studies in this research area were given in the paper. The main purpose of the research was to develop an integrated approach to determine the parameters of vacuum rectification of essential oils with obtaining pre-planned factions and carrying out the vacuum rectification of the essential oil under investigation according to the established parameters. Developing the integrated approach to determine the parameters of the vacuum rectification of essential oils to give pre-planned fractions was based on the fundamental laws of distillation and the component composition data of essential oils, according to which each essential oil can be conditionally divided into the sum of binary systems by key (target) components. This made it possible to plan the approximate composition of fractions and to establish a sequence of determining the parameters of the vacuum rectification of essential oil to obtain the planned fractions. This approach was used to determine the parameters of the vacuum rectification of Salvia sclarea essential oil, pre-examining its component composition by the gas chromatography. The conducted experiment allowed to adjust the theoretically calculated parameters of the vacuum rectification, to determine the operating conditions of selecting the planned fractions and changing their aromatic properties depending on the quantity selection limits. Carrying out the vacuum rectification of Salvia sclarea essential oil according to the established parameters has shown the possibility of obtaining pre-planned fractions and varying the release of various aromatic properties. The research results can be used in the technology of natural aromatic flavors while creating aromatic compositions with coordinated and harmonious flavor.